Western Balkans and Croatia Urbanization and Territorial Review - World Bank Group (World Bank, Washington, DC, 2019)
To accelerate growth and create jobs, the Western Balkans and Croatia will need faster economic growth generated by advanced industries and services that usually concentrate in cities. Raising the competitiveness of leading cities will thus be the priority for growth and job creation in the region. At the same time addressing the challenges of places left behind will be increasingly important for shared prosperity and sustainable growth. European Union (EU) accession, technological changes, and globalization are most likely to create growth opportunities that will favor cities and their agglomeration economies. These trends, if left unchecked, are also more likely to increase spatial welfare disparities. This report advocates for a stronger focus on cities, especially capital cities and their metro regions, as engines of growth and job creation. It also argues for policymakers to focus on lagging regions to address spatial welfare disparities likely to increase with the concentration of people and economic activity in fewer places.